Knowledge, attitudes, and practice of oncologists and oncology health care providers in promoting physical activity to cancer survivors: an international survey. - Hardcastle, Sarah; Kane, R.; Chivers, P.; Hince, D.; Dean, A.; Higgs, D.; Cohen, P. (Springer, 2018)
OBJECTIVE: To investigate knowledge, attitudes, and practices of oncologists towards physical activity (PA) in cancer survivors, and the association between oncologists' own PA behavior and PA promotion. METHODS: Oncologists (n?=?123) completed a survey based on the Theory of Planned Behavior (TPB). Participants reported PA promotion behavior, PA involvement, attitudes, intentions, social norm, perceived behavioral control (PBC), and confidence and knowledge of exercise prescription. Structural equation modeling (SEM) evaluated these associations. RESULTS: Less than half of oncologists reported regularly promoting PA to patients (46%), with 20% providing written information and 23% referrals. Only 26% were physically active. TPB SEM pathways explained 54.6% of the variance in PA promotion (comparative fit index (CFI)?=?0.905, standardized root mean square residual (SRMR)?=?0.040). Social norm was not only the significant pathway to intention but also a significant indirect pathway to PA promotion (p?=?0.007). Confidence to promote PA, PBC, and intentions were direct significant pathways to PA promotion (p?<?0.05). Exploratory SEM pathways explained 19.6% of the variance of PA behavior, which in turn explained 13.1% social norm, 10.7% attitude, 10.0% confidence to recommend, and 17.8% PA promotion behavior (CFI?=?0.921, SRMR?=?0.076). Instrumental attitude was a direct significant pathway to PA behavior (p?=?0.001). PA behavior was a direct significant pathway to social norms, attitude, confidence to recommend, and PA promotion (p?<?0.05). CONCLUSIONS: Oncologists reported a modest ability to promote PA, low PA promotion rates, and limited knowledge of exercise prescription. Patient physical activity promotion may be improved through strategies that increase oncologists' PBC, confidence, and their own personal PA participation.